The Effects of Tourism as 'Spiritus Movens' of the Croatian Economy - Ante Vuković; Tihomir Luković (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
According to the latest data for 2016, Croatian tourism accounts for 18.1% of Croatia's GDP. It puts it in the leading economic activity of Croatia. Tourism by the NKD is not one of the ten categorized classes of economic activity, but is a community of several subsectors and activities which we call tourism. Such shaped tourism as an activity has recently been promoted as a particularly significant Croatian economic activity. Given Croatia's share of GDP, Croatia is in the first place in Europe ahead of Malta 14.0% and Cyprus 12.8%, but it is the result of two contradictory forces, weak industry and economy in general, and high quality natural resources that are put into function as tourism. Here are some questions. If it is known that the effects of tourism can be direct and indirect, the question is how much the overall effects of tourism in Croatia. What is the real role of tourism and what opportunities are opening up, and as a key question is whethe r tourism can be an economic activity to which the long-term development of the Croatian economy can be based. Therefore, as a research objective it places valorization of the effects of tourism, especially indirect, and the research hypothesis is that tourism can be the spiritus movens of economic development, but not the backbone or foundation of macroeconomic development. In order to prove the hypothesis set up, the research will be done by the desk research method and based on this it will draw conclusions.
Keywords: 650; Tourism; Indirect effects; Macro model; Tourism perspective; Spiritus movens